Gamma Radiation for Preservation: A Novel Approach to Disinfect VHS Tapes in Historical Archives - Maria Luiza Emi Nagai; Djalma Dias; Pablo Vasquez (Brazilian Journal of Radiation Sciences)
Preserving historical artifacts, such as VHS tapes, in archival collections presents significant challenges, particularly in environments conducive to mold contamination. Inadequate control of temperature and relative humidity can promote mold growth, endangering the structural and informational integrity of these cultural assets. This study explores the application of gamma radiation treatment for the disinfection of mold-contaminated VHS tapes stored in historical archives. Utilizing the Multipurpose Gamma Irradiation Facility at the Institute of Energy and Nuclear Research (IPEN) in São Paulo, Brazil, we investigated the efficacy of gamma radiation in eradicating mold while preserving the tapes' mechanical properties and visual appearance. Despite the long-standing use of gamma ionization for decontamination since the 1960s, this research is novel in its focus on VHS tape preservation. Tensile tests and visual inspections were conducted on control, biodeteriorated, and gamma-irradiated samples. Results showed that gamma irradiation significantly improved tensile strength and strain in mold-contaminated tapes, with no observable changes in their visual appearance. This study contributes to the development of innovative preservation techniques, addressing the unique challenges posed by environmental factors in the storage of historical materials and underscoring the potential of gamma radiation as a dual-function method for disinfection and mechanical reinforcement.